2019
DOI: 10.3390/microorganisms7050128
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes and Acne Vulgaris: New Insights from the Integration of Population Genetic, Multi-Omic, Biochemical and Host-Microbe Studies

Abstract: The anaerobic bacterium Propionibacterium acnes is believed to play an important role in the pathophysiology of the common skin disease acne vulgaris. Over the last 10 years our understanding of the taxonomic and intraspecies diversity of this bacterium has increased tremendously, and with it the realisation that particular strains are associated with skin health while others appear related to disease. This extensive review will cover our current knowledge regarding the association of P. acnes phylogroups, clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
149
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(186 citation statements)
references
References 115 publications
(271 reference statements)
10
149
0
Order By: Relevance
“…On the other hand, a higher percentage of genus Staphylococcus in the majority of itchy skin of CKD patients, supporting the previous findings that members of the genus Staphylococcus frequently colonize itchy skin [87,88]. Results using multilocus sequence typing (MLST) and ribotyping analysis have shown that C. acnes with phylotype IA1/IC and III was globally associated with the severity of acne vulgaris, while phylotype II mostly colonizes healthy skin [89,90]. The constructed phylogenetic tree in Supplemental Figure S6 demonstrates that C. acnes we isolated from human skin shares the same branch and branch length with C. acnes phylotype II.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…On the other hand, a higher percentage of genus Staphylococcus in the majority of itchy skin of CKD patients, supporting the previous findings that members of the genus Staphylococcus frequently colonize itchy skin [87,88]. Results using multilocus sequence typing (MLST) and ribotyping analysis have shown that C. acnes with phylotype IA1/IC and III was globally associated with the severity of acne vulgaris, while phylotype II mostly colonizes healthy skin [89,90]. The constructed phylogenetic tree in Supplemental Figure S6 demonstrates that C. acnes we isolated from human skin shares the same branch and branch length with C. acnes phylotype II.…”
Section: Discussionsupporting
confidence: 79%
“…Future works will include evaluation of pharmacokinetics and stability of BA-NH-NH-BA in skin. Certain subtypes of opportunistic skin C. acnes bacteria are predominantly present in lesions of skin disorders such as acne vulgaris [89,90]. However, it has been illustrated that the abundance of C. acnes declined in dry and/or aged skin [63,64,95].…”
Section: Discussionmentioning
confidence: 99%
“…Altered follicular keratinization, increased and altered sebum production, C. acnes colonization, and inflammation are traditionally described as the key factors in the pathogenesis of acne. Nevertheless, the specific role of the skin commensal C. acnes in the whole disease process remains unclear ( McLaughlin et al., 2019 ). To this end, we studied the interaction process of C. acnes with its host, hereby focusing on potential differential interactions of C. acnes strains typically associated with acneic skin (type I) or with healthy skin (type II).…”
Section: Discussionmentioning
confidence: 99%
“…While recent evidence suggests that crosstalk between the host and its microbiome can be partly mediated by the sebaceous gland, the extent to which C. acnes contributes to acne remains to be unequivocally determined . After all, it is a commensal that also exerts beneficial effects …”
mentioning
confidence: 99%
“…7 After all, it is a commensal that also exerts beneficial effects. 8 Regardless of what will eventually supplant our current therapeutics, its development will require proper clinical outcome measures. 'Proper' in this context means quantitative, validated, including quality of life and internationally agreed upon.…”
mentioning
confidence: 99%